1972
DOI: 10.1172/jci106967
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of estrogen and synthetic anabolic hormone in postmenopausal osteoporosis

Abstract: A B S T R A C T In 29 women with postmenopausal osteoporosis, the proportion of total bone surface undergoing resorption or formation was evaluated by microradiography of iliac crest biopsy samples before and after shortterm (21-4 months) and long-term (26-42 months for estrogen and 9-15 months for anabolic hormone) treatment. After estrogen administration, values for boneresorbing surfaces decreased, although less prominently after long-term than after short-term therapy. The magnitude of this decrease was po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(57 citation statements)
references
References 16 publications
4
53
0
Order By: Relevance
“…The direct effects of androgens on bone metabolism in vivo have been extensively assessed in animal studies (largely rodents) (59)(60)(61)(62)(63)(64)(65) and clinical or epidemiological studies (5,7,8,(11)(12)(13)(14)(15). The endpoints of these studies were BMD (5, 7, 8, 11-13, 59, 64-66, 68-80), static or dynamic histomorphometry (7, 59-62, 64, 65, 67, 68, 87, 88), measurement of biochemical markers of bone formation and bone resorption (5,12,65,66,69,(81)(82)(83)(84)(85)(86)(87)(88), or biomechanical properties of bone (63).…”
Section: In Vivo Effects Of Androgens On Bone Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…The direct effects of androgens on bone metabolism in vivo have been extensively assessed in animal studies (largely rodents) (59)(60)(61)(62)(63)(64)(65) and clinical or epidemiological studies (5,7,8,(11)(12)(13)(14)(15). The endpoints of these studies were BMD (5, 7, 8, 11-13, 59, 64-66, 68-80), static or dynamic histomorphometry (7, 59-62, 64, 65, 67, 68, 87, 88), measurement of biochemical markers of bone formation and bone resorption (5,12,65,66,69,(81)(82)(83)(84)(85)(86)(87)(88), or biomechanical properties of bone (63).…”
Section: In Vivo Effects Of Androgens On Bone Metabolismmentioning
confidence: 99%
“…The endpoints of these studies were BMD (5, 7, 8, 11-13, 59, 64-66, 68-80), static or dynamic histomorphometry (7, 59-62, 64, 65, 67, 68, 87, 88), measurement of biochemical markers of bone formation and bone resorption (5,12,65,66,69,(81)(82)(83)(84)(85)(86)(87)(88), or biomechanical properties of bone (63). The majority of studies were performed either in spontaneous or orchiectomy-induced hypogonadism with or without subsequent androgen replacement therapy, or androgen treatment of eugonadal male or female subjects.…”
Section: In Vivo Effects Of Androgens On Bone Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In pre-and postmenopausal women, endogenous androgen levels correlate with BMD (25,26). Furthermore, a study comparing estrogen to a synthetic androgen in postmenopausal osteoporotic women showed that both steroids were equally effective in reducing bone resorption (27). Also, a 2-year double-blind trial showed that estrogen plus a non-aromatizable androgen significantly improved BMD over estrogen alone in surgically menopausal women (28).…”
Section: Introductionmentioning
confidence: 99%
“…Also, a 2-year double-blind trial showed that estrogen plus a non-aromatizable androgen significantly improved BMD over estrogen alone in surgically menopausal women (28). Therefore, exogenous androgens promote BMD maintenance in women when used alone (27) and in conjunction with estrogen (28).…”
Section: Introductionmentioning
confidence: 99%